FOOD PREFERENCES OF EARLY JUVENILE SCALLOPED SPINY LOBSTER IN EKAS BAY, LOMBOK, INDONESIA - Kawirian, Rizky Regina; Affandi, Ridwan; Mashar, Ali; Effendi, Irzal (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Ekas Bay is the largest bay on the island of Lombok which is the location for catching and cultivating spiny lobsters. This research was conducted from May to July 2021 on the Scalloped spiny lobster (Panulirus homarus). This study aims to identify the types of natural foods consumed and determine the preferred types of food, as well as the early juvenile feeding time of Scalloped spiny lobster located in Ekas Bay, East Lombok Regency, West Nusa Tenggara Province (NTB). Puerulus samples were collected in the last week of May 2021, enlarged puerulus was performed in submerged cages measuring 15 cm × 15 cm × 15 cm, mesh size <3 mm, with a density of 4 puerulus/m2. The cages are placed at a location 70 m to the sea from the shoreline, at a depth of 0.5, 1.0, and 1.5 m. After reaching the juvenile phase, lobsters are collected during the new and full moon phases (06.00 am, 06.00 pm and 12.00 am, respectively) in June to July 2021. A total of 60 individual juvenile lobsters (algal phase) were analyzed for their stomach contents. The average percentage of the total Index of Relative Important (IRI) obtained for the identified taxa were bivalves (22.32%), copepods (23.64%), demosponges (24.98%), while digestibdle material was 29.06%. The electivity index data (Ei) shows that lobsters prefer bivalves over other taxa. Lobster samples taken in the morning had a stomach fullness rate of 50%, indicating active feeding at night.